Katechismus-Andachten (1656) Kritische Ausgabe und Kommentar. Kritische Edition des Notentextes - Rist, Johann (Neudrucke deutscher Literaturwerke. N. F., 2016)
The Catechism Devotions are comprised of 50 spiritual songs that impart all of the material in Luther`s Small Catechism in vocal form. They are regarded as an important milestone in early modern theologia catechetica that aimed at an elemental presentation of the liturgy.